Corporate Social Responsibility and Corporate Risk: Evidence from European - Zhao, Tianqi (2022)
In recent years, global warming, the widening gap between the rich and the poor, environmental degradation and the inequitable distribution of social resources caused by industrial production have prompted people to think about corporate social responsibility. For firms, on the other hand, firm risk is both a comprehensive measure of aspects such as operations and finance and an important consideration for management in strategy formulation. A lower level of risk enables firms to make more accurate projections of future cash flows and facilitates better planning and implementation; a higher level of risk undermines forecasting and planning activities and requires firms to be alert to potential downsides. The impact of CSR on corporate risk is thought-provoking. This paper analyses the relationship between CSR and corporate risk through theoretical and empirical research and draws the following conclusions. By taking an active role in social responsibility, companies can reduce their sensitivity to market changes and mitigate their systemic risk. With the size of the company has a moderating influence on the relationship between CSR and corporate risk. The larger the size of the company, the greater the role of social responsibility in risk reduction. The role of social responsibility in reducing risk in controversial industries is not significant, but it can significantly reduce corporate risk in non-controversial industries. Recommendations are made based on the findings of this paper.